2020
DOI: 10.1111/imm.13280
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine‐regulated Th17 plasticity in human health and diseases

Abstract: Orchestra of cytokines regulates phenotypic and functional plasticity of non‐pathogenic and pathogenic Th17 cells in human health and diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 165 publications
(325 reference statements)
2
56
0
Order By: Relevance
“…These are substrates for the serine kinases DYRK1A and HIPK2, which cause IDD, ASD, and abnormal feeding behavior when mutated 122124 . DYRK1A also has important effects on innate immunity by regulating the balance between Th17 and T regulatory (Treg) cells, T cell subsets involved in the development of autoimmune diseases and inflammation 125129 . Interestingly, Th17 mediates the effects of Streptococcus on neuroinflammation in a mouse model of PANDAS by causing a breach in the BBB, with subsequent brain infiltration of Th17 lymphocytes 125, 130132 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are substrates for the serine kinases DYRK1A and HIPK2, which cause IDD, ASD, and abnormal feeding behavior when mutated 122124 . DYRK1A also has important effects on innate immunity by regulating the balance between Th17 and T regulatory (Treg) cells, T cell subsets involved in the development of autoimmune diseases and inflammation 125129 . Interestingly, Th17 mediates the effects of Streptococcus on neuroinflammation in a mouse model of PANDAS by causing a breach in the BBB, with subsequent brain infiltration of Th17 lymphocytes 125, 130132 .…”
Section: Discussionmentioning
confidence: 99%
“…DYRK1A also has important effects on innate immunity by regulating the balance between Th17 and T regulatory (Treg) cells, T cell subsets involved in the development of autoimmune diseases and inflammation 125129 . Interestingly, Th17 mediates the effects of Streptococcus on neuroinflammation in a mouse model of PANDAS by causing a breach in the BBB, with subsequent brain infiltration of Th17 lymphocytes 125, 130132 . HIPK2 regulates PPM1D protein levels by inducing its degradation in DNA-damaged cells, triggering activation of the DNA repair pathway 133 .…”
Section: Discussionmentioning
confidence: 99%
“…Th17 cells are an important T cell subpopulation linked with asthma and airway inflammation. These cells are known to secrete, among others, IL-17 [142]. In a study by Al-Harbi et al [119], the authors demonstrated an increase in the total number of Th17 cells and reduced expression of IL-17A and IL-23 after SFN-dependent Nrf2 activation in a mouse model of mixed granulocyte airway inflammation.…”
Section: T Lymphocytesmentioning
confidence: 97%
“…Th17.1 cells show stronger pro-inflammatory properties, supported by higher proliferation ability in response to T cell receptor (TCR) signals, higher GM-CSF, CCL20 and IL-22 production ( 178 , 179 ). A latest study, tracking the plasticity of Th17 cells in periodontitis model, suggested that the transformation of classical Th17 cells to ex-Th17 cells occurs during the conversion from acute inflammation to chronic inflammation ( 180 ).…”
Section: Regulators Of Th17 Cells Differentiationmentioning
confidence: 99%